Інтелігенція та розвиток заповідної справи в УРСР у 1950–1970-х рр. - Pagirya, Albina; Пагіря, Альбіна (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Досліджено участь української радянської інтелігенції та держави в організації заповідників на території УРСР у 1950–1970-х рр., а також боротьбу громадськості за охорону навколишнього середовища в межах заповідних зон.The development of historical and traditional direction for nature conservation - protected areas - in Ukraine in 1950-1970-th years in terms of party and Soviet totalitarian understanding of environmental policy was inefficient and highly controversial.
Intelligentsia and Nature Protection in Ukrainian Soviet Socialistic Republic in 1950–1970th.
Keywords: інтелігенція; заповідники; екологія; охорона природи; УРСР; intelligentsia; national park; nature protection; Ukrainian Soviet Socialistic Republic